Validation study of the apathy motivation index in French adults - Corveleyn, Xavier; Corbel, Camille; Fabre, Roxane; Zeghari, Radia; Dujardin, Kathy; Robert, Philippe; Manera, Valeria (Frontiers in Psychology, 2023)
Objective Apathy is present in many brain disorders, but it is also prevalent to varying degrees in healthy people. While many tools have been developed to assess levels of apathy in pathology, no standardized measure of apathy in healthy people exists. Method Therefore, this study aimed to validate the French version of the Apathy Motivation Index (f-AMI). The results of 729 participants were analyzed using an exploratory factorial analysis. Results Preliminary analyses suggested that the three domains of apathy extracted in the original AMI scale—behavioral activation (BA), social motivation (SM), and emotional sensitivity (ES)—could be found also in the f-AMI. A further exploratory analysis showed that a higher number of factors could be extracted, particularly for women. Specifically, both social and emotional factors could be divided into two sub-factors: (1) social motivation toward strangers or toward an acquaintance and (2) self-directed emotional sensitivity directed toward others. Regarding construct validity, the scores of f-AMI were correlated with the French Dimensional Apathy Scale results. Concerning the divergent validity, emotional sensitivity in apathy is different from depression, anhedonia, and fatigue levels. Conclusion These results suggest that the f-AMI can be used to assess levels of apathy in healthy adults.